2006
DOI: 10.1007/s10265-006-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and differential expression of an γ-aminobutyrate transaminase gene, OsGABA-T, in rice (Oryza sativa) leaves infected with blast fungus

Abstract: gamma-Aminobutyrate transaminase (GABA-T) catalyzes the conversion of GABA to succinic semialdehyde. Using differential display PCR and cDNA library screening, a full-length GABA-T cDNA (OsGABA-T) was isolated from rice (Oryza sativa) leaves infected with an incompatible race of Magnaporthe grisea. The deduced amino acid sequence comprises 483 amino acid residues and shares 85-69% identity with GABA-T sequences from other plants. OsGABA-T expression is induced by blast fungus infection, mechanical wounding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Glutamate levels were gradually decreased starting from the 1st day of the harpin infiltration and declined to the lowest levels of all groups. Similar to our results GABA levels were increased upon Cladosporium fulvum and P. syringae infection in tomato and A. thaliana and GABA shunt is activated by blast fungus infection in rice (Solomon and Oliver 2002;Wu et al, 2006;Park et al, 2010). Chevrot et al (2006) also found a rapid decrease in glutamate content which was associated with the increase in the GABA levels of tomato plants infected by A. tumefaciens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Glutamate levels were gradually decreased starting from the 1st day of the harpin infiltration and declined to the lowest levels of all groups. Similar to our results GABA levels were increased upon Cladosporium fulvum and P. syringae infection in tomato and A. thaliana and GABA shunt is activated by blast fungus infection in rice (Solomon and Oliver 2002;Wu et al, 2006;Park et al, 2010). Chevrot et al (2006) also found a rapid decrease in glutamate content which was associated with the increase in the GABA levels of tomato plants infected by A. tumefaciens.…”
Section: Discussionsupporting
confidence: 92%
“…In the studies mentioned above (Solomon and Oliver 2002;Wu et al, 2006;Park et al, 2010) high levels of GABA might be related to the increased activities of GDH and GAD enzymes. Taking this into account in the present study, we measured the activities of GDH and GAD enzymes and the expression profiles of the genes encoding these enzymes.…”
Section: Discussionmentioning
confidence: 94%
“…However, the upregulation of non‐PR genes suggested that tomato plants might use additional defense responses to cope with Bt infestation. Such is the case of the GABA transaminase subunit precursor, which was found to be induced in rice ( Oryza sativa ) leaves infected with an incompatible race of Magnaporthe grisea (Wu et al 2006). A contrasting possibility is that an upregulated expression GABA transaminase leading to the degradation of GABA, a potential control agent in plant‐invertebrate pest systems (Bown et al 2006; Shelp et al 2006) might favor rather than deter Bt infestation.…”
Section: Discussionmentioning
confidence: 99%
“…At GABA-T knockout mutants have been characterized and found to contain a reduced seed generation phenotype (Palanivelu et al , 2003). More recently, two homologous GABA-T genes have been identified in rice (Ansari et al , 2005; Wu et al , 2006), and another in pepper (GenBank accession number AAC78480). Interestingly, the pepper gene and one of the rice genes ( Osl2 ) lack sequences encoding an N-terminal targeting presequence, making cytosolic localization likely, although neither gene product has been tested for GABA-T activity nor has its location been confirmed experimentally.…”
Section: Introductionmentioning
confidence: 99%